Pengembangan Media Pembelajaran Berbasis Website pada Materi Hardware Kelas VIII di SMP Negeri 21 Samarinda - Yudha Alif Fauzi; Galih Yudha Saputra; Eko Subastian (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study aims to produce a product in the form of learning media based on the renderforest website which is feasible as a medium for learning informatics for junior high school grade VIII in Samarinda. This research uses the type of Research and Development (R&D) research with the PPE model which consists of three stages namely Planning, Production and Evaluation. The research subjects involved 3 media experts and 1 material expert. The object of research is renderforest teaching materials on hardware material. The results showed that the development of renderforest tested by 3 media expert validators received a value of 164 which indicates the category “very feasible” to use. Testing by 1 material expert gets a percentage value of 60 which indicates the category “very feasible” to use. Thus, the development of renderforest on class VIII software material in Samarinda developed with the PPE model is declared very feasible based on the feasibility test of media and material experts.